Treasures of the Southern sky - Gendler, Robert (Springer, 2011)
In these pages, the reader can follow the engaging saga of astronomical exploration in the southern hemisphere, in a modern merger of aesthetics, science, and a story of human endeavor. This book is truly a celebration of southern skies. Jerry Bonnell, Editor - Astronomy Picture of the Day. The southern sky became accessible to scientific scrutiny only a few centuries ago, after the first European explorers ventured south of the equator. Modern observing and imaging techniques have since revealed what seems like a new Universe, previously hidden below the horizon, a fresh astronomical bounty of beauty and knowledge uniquely different from the northern sky. The authors have crafted a book that brings this hidden Universe to all, regardless of location or latitude. Treasures of the Southern Sky celebrates the remarkable beauty and richness of the southern sky in words and with world-class imagery. In part, a photographic anthology of deep sky wonders south of the celestial equator, this book also celebrates the human story of southern astronomy with an engaging and detailed history of key contributors to southern sky exploration. The accompanying text provides the reader with intriguing facts and useful information about the featured objects. The volume is arranged by southern hemisphere season and brings to the printed page many of the most provocative and beautiful astronomical images of our time, many in print for the first time. The collection of imagery covers a full range of deep sky astronomical objects, including the familiar and iconic as well as those that are more obscure but no less intriguing. Masterful, state of the art professional and amateur astrophotography highlights the authors' carefully selected deep sky "treasures."